Modern Pharmacological Approaches to Therapies: Substances Tested in Animal Models of Rheumatoid Arthritis - Bauerova, Katarina; Poništ, Silvester; Nosaľ, Radomir; Stančikova, Maria; Rovensky, Jozef (IntechOpen, 2012)
None